Frontispiece: A Polymer Solution To Prevent Nanoclustering and Improve the Selectivity of Metal Nanoparticles for Electrocatalytic CO2 Reduction. Issue 44 (21st October 2019) - Zhang, Lei; Wei, Zichao; Thanneeru, Srinivas; Meng, Michael; Kruzyk, Megan; Ung, Gaël; Liu, Ben; He, Jie
Abstract : CO 2 Reduction . Polymeric N‐heterocyclic carbene (NHC) ligands are demonstrated to improve catalytic efficiency and lifetime of Au and Pd nanocatalysts for CO2 electroreduction by B. Liu, J. He et al. in their Research Article on page 15834 ff.